1997
DOI: 10.1017/s0007114500002853
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of an oral load affects chylomicron size in human subjects

Abstract: HDL-phospholipids are determinants in reverse cholesterol transport. They are mostly derived from triacylglycerol (TG)-rich lipoproteins. Chylomicron size is important, therefore, because it is related to the ratio surface phospholipids: core TG and, thus, determines the availability of postprandial phospholipids for transfer to HDL. Eleven healthy young women each ingested four different fat loads supplemented with retinyl palmitate and containing 60 g sunflower oil (SO), oleicsunflower oil (OSO), mixed oil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 51 publications
(49 reference statements)
1
28
0
3
Order By: Relevance
“…More recently, studies that have measured changes in different lipoprotein subfractions have revealed important differences with lipemic responses being of the order saturated fatty acid (SFA)4monounsaturated fatty acid (MUFA)4PUFA (Jackson et al, 2002a, b;Jackson et al, 2005). It is important to note that the physicochemical characteristics of the meal-fat mixture, linked to the fatty acid composition, could be a highly determinant of the rate of digestion and absorption, thus on the extent and/or kinetic of the postprandial lipid response (Sakr et al, 1997;Armand et al, 1999). N-3 PUFAs can lower the postprandial triglyceride response if sufficient amount is present within the test meal (Zampelas et al, 1994a), but levels used were far greater than those which would be consumed by most populations.…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, studies that have measured changes in different lipoprotein subfractions have revealed important differences with lipemic responses being of the order saturated fatty acid (SFA)4monounsaturated fatty acid (MUFA)4PUFA (Jackson et al, 2002a, b;Jackson et al, 2005). It is important to note that the physicochemical characteristics of the meal-fat mixture, linked to the fatty acid composition, could be a highly determinant of the rate of digestion and absorption, thus on the extent and/or kinetic of the postprandial lipid response (Sakr et al, 1997;Armand et al, 1999). N-3 PUFAs can lower the postprandial triglyceride response if sufficient amount is present within the test meal (Zampelas et al, 1994a), but levels used were far greater than those which would be consumed by most populations.…”
Section: Dietary Fatty Acidsmentioning
confidence: 99%
“…Thus, lipid moieties are organized in different kind of complex structures (emulsified droplets with different compositions and sizes, multilamelar structures, vesicles) that will determine the rate of fat digestion by gut lipases (Armand et al, 1996(Armand et al, , 1999. This can affect the rate of gastric emptying as well as kinetics of postprandial occurrence of chylomicrons in the circulation (Sakr et al, 1997;Armand et al, 1999). Great care should be taken on this aspect in designing test meals and postprandial studies.…”
Section: Physicochemical Properties Of Test Mealsmentioning
confidence: 99%
“…Rather, lipid transfer to the plasma compartment seemed accelerated, probably due to glucocorticoid effects on the GI motor complex (27,28).This suggests that fewer but larger, i.e. fat-richer, chylomicrons are generated after ACTH administration (29,30). In fact, the observation that dietary markers did not display similar postprandial plasma patterns as ApoB-48 is consistent with the view that the lipid-lowering effect of ACTH is due to direct inhibition of ApoB synthesis, since the decreased secretion of lipoproteins does not seem to result from decreased lipid availability.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Thomsen et al (1999Thomsen et al ( , 2003 reported lower plasma TAG levels after consumption of a high-MUFA meal compared with a high-saturated fatty acids (SFA) meal. In contrast, other studies have shown that meals or fat emulsions rich in MUFA produce higher postprandial TAG compared with SFA (Higashi et al, 1997;Sakr et al, 1997;Mekki et al, 2002). Finally, other studies have demonstrated that replacement of SFA with MUFA in acute test meals does not influence postprandial plasma TAG metabolism Jackson et al, 1999Jackson et al, , 2002.…”
Section: Introductionmentioning
confidence: 98%